Environmental pollution and medicinal plants : impact and adaptation - Husen, Azamal (Boca Raton : CRC Press, 2022)
"Environmental pollution mainly caused by anthropogenic activities can damage medicinal plants and alter their growth, gas exchange parameters, biochemical attributes, bioactive substances, antioxidant activity, and gene expression. This book presents information on impacts of environmental pollution on the performance of medicinal plants at various levels including damage detection, adaptation, tolerance, physiological and molecular responses. Discusses trends and responses of medicinal plant tolerance and adaptation to environmental pollution. Focuses on secondary metabolites, phytochemicals, and bioactive compounds associated with medicinal plants growing in contamination conditions"--
Potential impacts of environmental pollution on growth and metabolism of medicinal plants / Nisha Rani, Madhavi Joshi, , Anand Sagar, Hardeep Rai Sharma -- Growth and development of medicinal plants, and production of secondary metabolites under ozone pollution / Deepti, , Archana (Joshi) Bachheti, Piyush Bhalla, Rakesh Kumar Bachheti, Azamal Husen -- Impact of UV radiation on growth and pharmaceutical properties of medicinal plants / Deepti, Archana (Joshi) Bachheti, Kiran Chauhan, Rakesh Kumar Bachheti, Azamal Husen -- Impact of sulfur dioxide deposition on medicinal plants growth and production of active constituents / Shakeelur Rahman, Azamal Husen -- Effect of elevated CO2 conditions on medicinal plants : a relatively unexplored aspect / Anuj Choudhary, Antul Kumar, Harmanjot Kaur, Mandeep Singh, Gurparsad Singh Suri, Gurleen Kaur, and Sahil Mehta -- Water pollution and medicinal plants : insights into the impact and adaptation responses / Antul Kumar, Anuj Choudhary, Harmanjot Kaur, Ritesh Kumar, Radhika Sharma, Himani Gautam and Sahil Mehta -- Impact of industrial wastewater on medicinal plant growth / Shipra Jha, Paras Porwal -- Heavy metal pollution and medicinal plants : an overview / Allah Ditta, Naseer Ullah, Xiaomin Li, Ghulam Sarwar Soomro, Muhammad Imtiaz, Sajid Mehmood, Amin Ullah Jan, Muhammad Shahid Rizwan, Muhammad Rizwan, Iftikhar Ahmad -- Environmental pollution influences the secondary metabolite production in medicinal plants / Swati T. Gurme, Mahendra L. Ahire, Jaykumar J. Chavan, Pankaj S. Mundada -- Biotechnological studies of medicinal plants to enhance production of secondary metabolites under environmental pollution / Saumya Pandey -- Understanding the metabolomics of medicinal plants under environmental pollution : challenges and opportunities / Prachi Sao, Rahat Parveen, Aryan Khattri, Shubhra Sharma, Neha Tiwari, Sachidanand Singh -- Understanding the proteomics of medicinal plants under environmental pollution : challenges and opportunities / Pooja Singh, V.K. Mishra, Rohit Kashyap, Rahul Rawat -- Genome editing strategy for medicinal plants growing under adverse environmental pollution : challenges and opportunities / Arvind Arya.
Includes bibliographical references and index.
Keywords: Medicinal plants -- Effect of pollution on